Spatial Analysis of Determinants of Filariasis-Endemic Areas in West Sumatra - Masrizal, Masrizal; Diana, Fivi Melva; Rasyid, Rosfita (UI Scholars Hub, 2017)
West Pasaman District and Agam District are filariasis-endemic areas in West Sumatra with prevalence of 12.40 per 100,000 cases and 11.27 per 100,000 cases respectively. This study aimed to determine risk factors associated with the prevalence of filariasis and mapping the vulnerability of the area in West Sumatra. A case control study design was conducted in the West Pasaman District and Agam District. The study used a sample of 74 cases and 74 controls taken by simple random sampling for the case and purposive random sampling for control. Data analysis used univariate, bivariate, multivariate and spatial. The results in Agam District showed that variables associated relation with filariasis (p value < 0.05) were the level of knowledge, plantations, the paddy, the ceiling of the house. The most dominant risk factor was knowledge. Type of vector that was found was Culex. While in West Pasaman District, the variable associated with filariasis (p value < 0.05) was the use of mosquito nets, the habit of dressing, marshes, and ceiling. The most dominant risk factor was the ceiling of the house.